New strategies in the preparation of exfoliated thermoplastic starch-montmorillonite nanocomposites - Aouada, Fauze Ahmad [UNESP]; Mattoso, Luiz H. C.; Longo, Elson [UNESP] (Elsevier B.V., 2011)
A simple method based on the combination of the intercalation from solution and melt-processing preparation methods was used to prepare highly exfoliated and compatible thermoplastic starch (TPS) and montmorillonite clay (MMT) nanocomposites. The effects of the MMT content on the thermal, structural, and mechanical properties of the nanocomposites were investigated. XRD diffraction was used to investigate the MMT exfoliation/intercalation degrees in the TPS matrix. Data from thermogravimetric analysis and differential scanning calorimetry revealed that the addition of MMT increased the thermal stabilities of TPS nanocomposites. Young's modulus and tensile strength increased from 8.0 to 23.8 MPa and 1.5 to 2.8 MPa with an increasing MMT content from 0 to 5 wt% without diminishing their flexibility. The improvement in such properties can be attributed to the good dispersion/exfoliation of MMT in the TPS matrix. Combining both methods, it was possible to obtain homogenous and transparent nanocomposites with excellent thermal and mechanical properties for application as packaging materials. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Intercalation from solution; Mechanical properties; Melt-processing; Montmorillonite clay; Thermal properties; Thermoplastic starch